Program Pengadaan Tempat Sampah di Kelurahan Klawuyuk dan Sekolah Dasar Islam Terpadu Daarul Fikri Cendekia - Fajri Yasin, Azalia; Rumakat, Fatmawati; Way, Demson; Jitmau, Apolos M.H. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Cleanliness is one of the problems that has no end. To help improve cleanliness, the procurement of trash bins is held to support environmental cleanliness. Trash bins have an essential role as a medium for waste management in every environment. The purpose of this activity, which is also part of the Real Work Lecture Program (KKN), is to find a solution to the problem of environmental pollution in Klawuyuk Village, including in the Klawuyuk Village Office and Integrated Islamic Elementary School Daarul Fikri Cendekia. In conclusion, this program highlights the actual contribution of KKN students in building team cooperation, community participation, and educational roles as a concrete step in creating a clean, healthy, and sustainable environment.